Membangun E-commerce Spare Parts Mobil pada Toko Aneka Jaya Motor - Nurhidayat, Sodik; Rusli, Muhammad (KALBISCIENTIA Jurnal Sains dan Teknologi, 2020)
Aneka Jaya Motor is company engaged in the business of selling car spare parts in Bekasi.At present Aneka Jaya Motor shop is only a shop, so the buying and selling process only occurs in theshop. Iin the current system there are many obstacles, such as the difficulty of promotion Aneka JayaMotor goods to many customers, because so far the bidding and transactions have been done manually,which only relies on the buyer to come directly to the store. In conducting this research, the type ofresearch use is qualitative research with the research method used in this research is Waterfall withsystem requirements, system analysis, system design with UML modelling and system implementationusing PHP and MySQL and tested using the blackbox testing method. The results in this study are thecreation of e-commerce information systems for selling car spare parts based website at Aneka JayaMotor store that helps the sales process and makes it easy to transact long distances with Aneka JayaMotor customers.